2013
DOI: 10.2147/prbm.s40460
|View full text |Cite
|
Sign up to set email alerts
|

Major factors for facilitating change in behavioral strategies to reduce obesity

Abstract: It is very unlikely that our obesity-promoting environment will change in the near future. It is therefore mandatory to improve our knowledge of the main factors associated with successful adoption of obesity-reducing behaviors. This may help design more powerful procedures and strategies to facilitate the adoption of healthy lifestyles in a “toxic” environment favoring the development of a positive energy balance. The aim of this review is to describe the main factors associated with successful adoption of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 95 publications
1
55
0
1
Order By: Relevance
“…In line with the present research, some studies have shown that lack of social support challenges the formation of health behaviors (19,20). Other surveys have reported that the patients' lack of knowledge (22), absence of psychological readiness and motivation for communication (23), lack of interest in changing the behavior (24,25), and financial and cultural (26) concerns of the clients to receive services are principal barriers to health education. To provide better health services to the clients and increase the efficiency of the presented education, it is essential that all health caregivers, educational authorities, and health care providers learn communication and counseling skills.…”
Section: Discussionsupporting
confidence: 86%
“…In line with the present research, some studies have shown that lack of social support challenges the formation of health behaviors (19,20). Other surveys have reported that the patients' lack of knowledge (22), absence of psychological readiness and motivation for communication (23), lack of interest in changing the behavior (24,25), and financial and cultural (26) concerns of the clients to receive services are principal barriers to health education. To provide better health services to the clients and increase the efficiency of the presented education, it is essential that all health caregivers, educational authorities, and health care providers learn communication and counseling skills.…”
Section: Discussionsupporting
confidence: 86%
“…It is essential that areas of user interface and evidence-based methods marry in a way not to compromise one another. Websites should remain simple, provide strong tutorials, avoid repetition, use evidence-based strategies with increasing intensity and offer rewards in order to keep subjects engaged and promote adherence (5,17). Given that wide-scale implementations of web-based programs often suffer from early technical glitches that may affect consumer morale, such programs should be rolled-out gradually (29).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…The increasing prevalence of obesity over the recent decades appears to be in large part due to behavioral changes supporting the maladaptive behaviors of sedentariness and consumption of larger, energy-dense foods (5). Behavior-based weight loss interventions are part of a comprehensive lifestyle approach used in the management of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological approach was based on the cognitive-behavioral therapy of obesity [24] as well as a systemic/strategic approach [25]. Psychological individual sessions initially aimed at a diagnostic assessment and to the listing of weight-related problems [26].…”
Section: Methodsmentioning
confidence: 99%